Development of Antibody-Based Approaches for Specific Detection and Treatment of Triple Negative Breast and Ovarian Cancers - Hussain, Ahmad Fawzi; Justus Liebig University Giessen (My University, 2024)
The hypothesis of a ‘‘one pill fits all’’ limits the success of cancer treatments and it is now acknowledged that no single therapeutic agent has the same effect on all patients with the same diagnosis. Precision medicine is a promising paradigm, mainly in cancer treatment, and it is widely believed that precision medicine will have a revolutionary impact on healthcare before, during and after disease by specifically targeting disease cells to ensure maximal efficacy and safety. However, the heterogeneity and complexity of tumors, along the development of different metastases set a countless challenge for cancer targeting therapies. The considerable increase in understanding molecular processes led to identification of numerous biomarkers for cancer detection and treatment. These biomarkers have paved the way for developing several tumor targeting therapies in recent years. It is now becoming increasingly clear that corresponding therapies have a great chance in improving cancer care by selectively targeting tumor cells and concomitantly reducing adverse side effects. Despite recent reduction in breast cancer mortality, breast cancer remains the leading cause of cancer-related death among women worldwide. Breast cancer targeted therapies that rely on tumor cell expression of estrogen (ER), progesterone (PgR) and HER2 receptors can be effective in the treatment of luminal and HER2-positive breast cancers. However, TNBC presents a challenge as it is characterized by the absence of ER, PgR and HER2 receptors. TNBC patients are generally young premenopausal women accounting for up to 20% of breast cancer cases. Moreover, TNBC is associated with unfavorable outcome with decreased disease free and overall survival rates. Ovarian cancer is one of the most common gynecological tumors worldwide. The gold standard therapy for ovarian cancer involves an intensive surgical cytoreduction, followed by a platinum and taxane-based cytostatic treatment. The antiangiogenetic bevacizumab and / or the novel drug class of PARP inhibitors – both effective in some high-grade serous cancers – have improved the progression-free survival as well as the overall survival. Nevertheless, the prognosis of ovarian cancer is poor and new therapeutic approaches warranted. The fatality rate of ovarian cancer is high because the available therapeutic modalities have failed to treat ovarian cancer patients with advanced disease, who are representing more than 70% of patents with ovarian cancer. For these patients, the five-year survival rates are ranging from 20% to 30%, in some settings up to 50%, compared to cure rates of 70% to 90 cure rates for those diagnosed with the disease is confined to the ovary. This is mainly due to the spreading of ovarian tumors into the peritoneum, retroperitoneal space and the serosa layer of the gut, which is one of the major limitations preventing the removal and / or treatment of poor-vascularized macro-metastasis, local and/or long distant micro-metastases as well as non-resectable macro-metastasis during cytoreductive surgery. These untreated tumor tissues usually cause tumor relapse, reducing the median survival rate from ~99 months for the patient with no residual disease to ~36 months if residual tumors are present. The high inter- and intra-tumor heterogeneity of TNBC and ovarian cancer associated with different histopathological features and clinical behaviors that influence differentially the therapeutic outcome of surgery and/or chemotherapy and associated with inherent and acquired drug resistance. Therefore, there is there is an urgent, and till now unmet, medical need for new treatment options for TNBC and ovarian cancer. This work represents the attempts to refine the methods for generating cancer targeting therapy and to overcome the shortcomings of the available therapeutic modalities of TNBC and ovarian cancer, such as tumor heterogeneity, low efficiency, and drug resistance. This is mainly achieved by using SNAP-tag technology as a site-specific conjugation method for arming antibody with therapeutic and / or imaging agents. Moreover, applying different therapeutic strategies (near infrared photo-immunotheranostics (NIR-PIT), antibody drug conjugate (ADC), and immunotoxin) as well as targeting different highly expressed cell surface receptor (EGFR, EpCam and CSPG4) on TNBC and ovarian cancer cells. SNAP-tag technology allows to site-specifically conjugate a wide range of effector molecules rapidly and efficiently under physiological conditions with 1:1 conjugation stoichiometry. The different mechanism of actions can overcome the limitation of cancer cell acquired and inherited drug resistance of TNBC and ovarian cancer, while targeting a set of different cell surface receptor can overcome the inter- and intra-tumor heterogeneity of TNBC and ovarian cancer. The developed NIR-PIT and ADC reagents demonstrated strong imaging properties and / or potent therapeutic activity in combination and / or individually against different TNBC and ovarian cancer cells in vitro. Despite the impressive results, additional experiments are undoubtedly required to determine the pharmacokinetic properties and to verify the imaging and / or the therapeutic activity in vivo. In another therapeutic approach, two human-based immunotoxins, scFv-CSPG4-MAP and GbR201K-scFvEpCam (full human immunotoxin), were generated and evaluated. Both in vitro and in vivo results showed that the immunotoxins have a high translational potential for targeted elimination of TNBC. The impact of developing antibody-based recombinant proteins, the use of SNAP-Tag technology for conjugating effector molecules, targeting three cell surface receptors (EGFR, EpCam and CSPG4) in combination and / or individually and the exploiting of different therapeutic strategies (NIR-PIT, ADC, and immunotoxin) for targeting TNBC and ovarian cancer were investigated and discussed in this work.
Entwicklung Antikörper basierter Ansätze zur spezifischen Erkennung und Behandlung von Tripel-negativen Brust- und Eierstockkrebs
Keywords: ddc:610